2019
DOI: 10.1093/database/baz031
|View full text |Cite
|
Sign up to set email alerts
|

MSGP: the first database of the protein components of the mammalian stress granules

Abstract: In response to different stress stimuli, cells transiently form stress granules (SGs) in order to protect themselves and re-establish homeostasis. Besides these important cellular functions, SGs are now being implicated in different human diseases, such as neurodegenerative disorders and cancer. SGs are ribonucleoprotein granules, constituted by a variety of different types of proteins, RNAs, factors involved in translation and signaling molecules, being capable of regulating mRNA translation to facilitate str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
52
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(56 citation statements)
references
References 30 publications
2
52
0
2
Order By: Relevance
“…Also prevalent in plasma were RNA fragments containing binding sites for DHX30, a DExH-box RNA helicase; GRWD1, a histone-binding protein that may also play a role in ribosome assembly; ZNF622, a zinc-finger protein; BUD13, a spliceosome component; PPIG, a protein involved in protein-folding; and SERBP1, a mRNA-binding-protein. Notably, seven of these top 15 proteins (DDX3X, DDX6, DHX30, LARP4, SERBP1, SND1, and YBX3) are components of stress granules ( Markmiller et al, 2018 ; Nunes et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Also prevalent in plasma were RNA fragments containing binding sites for DHX30, a DExH-box RNA helicase; GRWD1, a histone-binding protein that may also play a role in ribosome assembly; ZNF622, a zinc-finger protein; BUD13, a spliceosome component; PPIG, a protein involved in protein-folding; and SERBP1, a mRNA-binding-protein. Notably, seven of these top 15 proteins (DDX3X, DDX6, DHX30, LARP4, SERBP1, SND1, and YBX3) are components of stress granules ( Markmiller et al, 2018 ; Nunes et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Many proteins involved in SG assembly are RNA binding proteins that favor mRNA stability (TIA-1, TIAR, HuR), mRNA metabolism (G3BP-1, G3BP-2, DDX6, SMN, Staufen1, DHX36, Caprin1, ZBP1, HDAC6, ADAR), signaling proteins (mTOR, RACK1) and interferon-stimulated gene (ISG) products (PKR, ADAR1, RIG-I, RNase L, and OAS (reviewed in Poblete-Durán et al, 2016). Recently, Nunes et al generated an open access electronic resource containing all SGs-recruited protein reported to date (available at https://msgp.pt/) (Nunes et al, 2019). Its assembly is typically a consequence of translation repression upon phosphorylation of the translation initiation factor eIF2α by environmental stress such as heat shock, UV irradiation, oxidative stress, viral infection, and even upon treatment with several drugs (see Table 1).…”
Section: Viral Families and Stress Granulesmentioning
confidence: 99%
“…Searching the Mammalian Stress Granules Proteome Database (https://msgp.pt) [102], we found that 18% of the SMCR8 proiein interactome (61/340) and 26% (35/ 201) of the C9orf72 interactome are known SGassociated proteins. It is thus possible that SG components bind endogenous SMCR8-C9orf72 complexes and shepherd them to SGs, although why this would not also be the case for overexpressed exogenous SMCR8 or C9orf72 proteins is unclear.…”
Section: Evidence That Endogenous Smcr8 Accumulates In Cytoplasmic Stmentioning
confidence: 99%